Examination of Autopsy Cases in the Period of 1990-1994 - Ege, Beyhan; Yemişçigil, Ali; Aktaş, Ekin Özgür; Koçak, Aytaç (The Bulletin of Legal Medicine, 1997)
In the period 1990-1994, legal investigations, autopsy, toxicology and histopathology reports of 2740 cases who autopsies were performed at Council of Forensic Medicine Izmir Group Chairmanship were evaluated according to age, sex, origin, death cause, result of toxicology and histopathologic analysis and blood alcohol levels. 78.3% of cases were male. The age group of 20-29 was the one most frequently seen. Morbid causes (33.3%) were primary, followed by homicides (28.9%), accidents (21.9%) and suicides (13.6%). In bloods of 16.1% cases various alcohol levels were detected. Compared by the result of similar studies, there exist some geographic differences among causes of deaths. We think that it would be appropriate to perform similar studies in different geographic portions of Turkey to determine the general status. Key words: Autopsy, Postmortem examination.